The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1046/j.1365-3059.2002.00744.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro inhibition of soil microorganisms by 2‐phenylethyl isothiocyanate

Abstract: Isothiocyanates (ITCs) are produced by the enzymatic hydrolysis of glucosinolates in cruciferous plants and can kill fungi, oomycetes and bacteria. The effect of 2-phenylethyl ITC (2-PE ITC), the main ITC liberated from the roots of canola, was tested in vitro on a range of fungi, oomycetes and bacteria. Bacteria were generally more tolerant than the eukaryotic pathogens to 2-PE ITC, although both groups showed considerable variability in response (ED 90 ranging from 0·005 to 1·5 m m for eukaryotes, and from 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(85 citation statements)
references
References 25 publications
4
80
1
Order By: Relevance
“…Differential effects on microbial populations that we observed could result from variable direct susceptibility of populations towards antimicrobial properties of hydrolysis products of glucosinolates (Smith and Kirkegaard, 2002;Kliebenstein et al, 2005;Brader et al, 2006). Beside their antimicrobial effect, glucosinolates and their hydrolysis products could also stimulate microbial growth.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Differential effects on microbial populations that we observed could result from variable direct susceptibility of populations towards antimicrobial properties of hydrolysis products of glucosinolates (Smith and Kirkegaard, 2002;Kliebenstein et al, 2005;Brader et al, 2006). Beside their antimicrobial effect, glucosinolates and their hydrolysis products could also stimulate microbial growth.…”
Section: Discussionmentioning
confidence: 77%
“…Fungi modifications are expected according to literature. They were reported to be more sensitive than bacteria to these compounds (Smith and Kirkegaard, 2002). The formation of antimicrobial products from glucosinolates has been also suggested to explain the inability of Brassicaceae plants to form arbuscular mycorrhizal (Vierheilig et al, 2000;Roberts and Anderson, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of glucosinolates in root tissues can reduce the growth of fungi and oomycetes (Smith and Kirkegaard, 2002). Larkin and Griffin (2007) reported that when rapeseed was grown as a green manure crop, it reduced powdery scab infections in a subsequent potato crop.…”
mentioning
confidence: 99%
“…However, Smith and Kirkegaard (2002) found out that species of Trichoderma genus are tolerant to the above compounds. Curl (1982) even stated that plant excretions can improve the phytosanitary condition of soils through a better development of fungi inhibiting the growth of pathogens.…”
Section: Resultsmentioning
confidence: 99%